Factors Associated with Renal Complications in Patients with Diabetes and Hypertension at Khong Chiam Hospital, Ubon Ratchathani Province - Longchin, Juthathip; Suebsamran, Phalakorn; Limpiteeprakan, Pawena (Health Science Journal of Thailand, 2024)
This research aims to study factors associated with kidney complications in diabetes and hypertension patients at Khong Chiam Hospital, Ubon Ratchathani Province. The sample consisted of 350 patients, selected through multi-stage sampling. Research tools included questionnaires on knowledge, personal perceptions, social support, and preventive behaviors, with reliability between 0.71-0.85. Data were analyzed using descriptive statistics and multiple logistic regressions, presenting results with Adjusted Odds Ratio (ORadj) and 95% confidence intervals at a 0.05 significance level. Results showed 26% of patients had kidney complications, with 50.6% having high personal perception levels, 81.7% perceiving complication severity as very high, and 34% perceiving prevention barriers as very low. Additionally, 80.9% received high social support, and 68.6% had good preventive behaviors. However, dietary behavior needed improvement (35.4%). Factors significantly associated with kidney complications (p<0.05) were gender (ORadj = 0.13, 95%CI: 0.03-0.59), age (ORadj = 0.15,95% CI: 0.03-0.71), monthly income (ORadj = 0.56, 95%CI: 0.12-0.56), time since diagnosis (ORadj = 8.81, 95%CI: 2.54-30.53), and preventive behaviors (ORadj = 0.02, 95%CI: 0.00-0.07). This research can be applied in chronic disease clinics of healthcare facilities with similar contexts to prevent and delay long-term kidney deterioration.